THE USE OF YOUTOBE MEDIA IN IMPROVING STUDENTS’ VOCABULARY THROUGH ONLINE LEARNING - Lestari, Anggun; Latifah, Nuri; Rahman, Arby Abdillah Muhammad (LINGUAMEDIA Journal, 2023)
The Use of YouTube Media in Improving Students' Vocabulary through Online Learning is the title of this article. One of the programs that can help students learn vocabulary and understand English online is YouTube. Based on these factors, this journal will analyze how students' success in mastering English vocabulary is affected by YouTube media.Ten students from grade 10 at MAN 1 Cirebon provided the data for this study, which is based on the results of the exams they took. After watching English-related YouTube videos, the students took an exam to determine their progress in learning new vocabulary in the language. Both quantitative and qualitative methodologies were used to analyze the data in this study.The research findings show that if YouTube is used consistently and effectively, it can improve word comprehension. Students can learn new English expressions and recognize new terminology by using YouTube programs repeatedly. In addition, YouTube applications can help students develop their speaking, listening, reading, and other skills in English.Students at MAN 1 Cirebon can better understand English and learn new vocabulary by using the YouTube application. This is evident from the observation results which show how students' language skills improved after watching English videos on the YouTube application in their spare time.